Incorporating genome-wide and transcriptome-wide association studies to identify genetic elements of longissimus dorsi muscle in Huaxi cattle - Liang, Mang; An, Bingxing; Deng, Tianyu; Du, Lili; Li, Keanning; Cao, Sheng; Du, Yueying; Xu, Lingyang; Zhang, Lupei; Gao, Xue; Cao, Yang; Zhao, Yuming; et al. (Frontiers in Genetics, 2023)
Abstract: Locating the genetic variation of important livestock and poultry economic traits is essential for genetic improvement in breeding programs. Identifying the candidate genes for the productive ability of Huaxi cattle was one crucial element for the subsequent breeding. Based on the genotypes and phenotypes data of 1478 individuals and the RNA-seq data of 120 individuals contained in 1478 individuals, we implemented genome-wide association studies (GWAS), transcriptome-wide association studies (TWAS), and Fisher's combined test (FCT) to identify the candidate genes for the carcass trait, the weight of longissimus dorsi muscle (LDM). The results indicated that GWAS, TWAS, and FCT identified seven candidate genes for LDM altogether, PENK was located by GWAS and FCT, PPAT was located by TWAS and FCT, and XKR4, MTMR3, FGFRL1, DHRS4, and LAP3 were only located by one of the methods. After functional analysis of these candidate genes and referring to the reported studies, we found that they were mainly functional in the progress of the development of the body and the growth of muscle cells. Combining advanced breeding techniques such as gene editing with our study will significantly accelerate the genetic improvement for the future breeding of Huaxi cattle.